2017
DOI: 10.15386/cjmed-652
|View full text |Cite
|
Sign up to set email alerts
|

A case control study of risk factors associated with pulmonary tuberculosis in Romania: Experience at a clinical hospital of pneumology

Abstract: Background and aimTuberculosis (TB) remains a major public health issue in Romania. The aim of the present study was to evaluate the potential demographic, socioeconomic and behavioral risk factors for TB among hospitalized patients in Romania.MethodsThis is a case-control study conducted between March 1st 2014 and March 30th 2015 at Leon Daniello Clinical Hospital of Pneumology, Cluj Napoca. A total of 150 TB patients defined as “cases” were matched for age, sex and county of residence to 150 controls selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
3
9
2
5
Order By: Relevance
“…Additionally, previous studies showed a statistically significant trend in the risk of TB with increasing number of CPD [10,11]. However, to the best of our knowledge, there is only one previous work that has focused on the threshold number of cigarettes, indicating that smoking more than 20 CPD was an independent factor associated with TB [12]. We found a significantly higher risk of TB for men smoking 20 or more CPD in comparison with nonsmoking individuals, but no significant difference between the latter and those smoking up to 20 CPD.…”
mentioning
confidence: 81%
“…Additionally, previous studies showed a statistically significant trend in the risk of TB with increasing number of CPD [10,11]. However, to the best of our knowledge, there is only one previous work that has focused on the threshold number of cigarettes, indicating that smoking more than 20 CPD was an independent factor associated with TB [12]. We found a significantly higher risk of TB for men smoking 20 or more CPD in comparison with nonsmoking individuals, but no significant difference between the latter and those smoking up to 20 CPD.…”
mentioning
confidence: 81%
“…After reading the full text, 57 studies were excluded for various reasons mentioned in Figure . Thus, 14 studies (eight cohort studies and six case‐control studies), published between 1992 and 2017, which involved 22 616 623 participants, met the eligibility criteria for this analysis .…”
Section: Resultsmentioning
confidence: 99%
“…Median follow‐up time in the cohort studies ranged from one to five years. Of the six case‐control studies, one (Denmark) was nationwide and one (Romania) was hospital‐based . All studies had adjusted the rate ratio or odds ratio at least for age, and some studies had adjusted for a variety of potential confounders, such as gender, ethnicity, body mass index (BMI), or socio‐economic status.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations